The association among perception of osteoarthritis with adverse pain anxiety, symptoms of depression, positive and negative affects in patients with knee osteoarthritis: a cross sectional study - Muhammad Aqeel; Tasnim Rehna; Rimsha Sarfraz (Journal of the Pakistan Medical Association, 2020)
Objective: To examine the association of perception of osteoarthritis with adverse pain anxiety, symptoms of depression, positive and negative affects inpatients with knee osteoarthritis, andto identify the prevalence of these parameters in male and female patients. Methods: The cross-sectional study was conducted at the Department of Orthopaedic Surgery, Pakistan Institute of Medical Sciences, Islamabad, Pakistan, from September 2017 to December 2018, and comprised osteoarthritis patients, aged 30-60 years. Psychiatric evaluation consisted of a semi-structured interview based on the Present Status Examination, and assessment was done using Beck Depression Inventory, Positive and Negative Affect Scale, Osteoarthritis Scale, and the Pain Anxiety Scale. Radiographic examination was done to evaluate knee osteoarthritis. Data was analysed using SPSS 20. Results: Of the 250 subjects 144(57.6%) were males and 106(42.4%) were females. The overall men age was 55.09+/-10.60 years. . The patients had a strong inclination to enhance psychiatric illnesses (p<0.05), and gender differences were significant in this regard (p<0.05). Conclusion: Osteoarthritis patients revealed high prevalence of pain anxiety, depression and mood swings. Male patients were predisposed more towards psychiatric features compared to females. Key Words: Knee osteoarthritis, Psychiatric features, Depression, Pain, Anxiety, Continuous...